MODEL PEMBELAJARAN BAHASA ARAB BERBASIS KONSTRUKTIVISME DI PERGURUAN TINGGI ISLAM - Isop Syafe’i (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This study aims to test and develop models of constructivism-based learning in learning Arabic for the Islamic university. The research utilized Research and Development (R&D) method. The research site chosen is UIN Sunan Gunung Djati Bandung. This university is one of Islamic Universities in Indonesia that requires the students to learn and master Arabic. The results showed that the constructivism-based learning model can improve the processes and outcomes of students’ skills in Arabic. The use of this model can also improve the performance of lecturers in terms of making 1) learning time more effective, 2) learning more focused and 3) learning activities more controlled. This model has made the achievement score of experimental group in post-test higher than that is of the control group as indicated in validity test. These findings indicate that the constructivism-based learning model is effective in improving students’ skills in Arab ccompared to students’ skills in Arabic learning through conventional learning model. It implies that other Islamic universities in Indonesia can also implement this constructivism-based learning model.